Estrutura genética populacional de Heliconius erato e Heliconius melpomene (Lepidoptera: Nymphalidae) em fragmentos de Mata Atlântica do Rio Grande do Norte - Moura, Priscila Albuquerque de (2009)
Extensive studies using molecular markers on butterflies have shown how a highly fragmented landscape may result in the reduction of gene flow among patches of habitat and, consequently, increase genetic differentiation among populations. However, little is known about Heliconius geographical structure and the effects of fragmentation on the connectivity of populations. Furthermore, findings on the effects of the population structure on the dynamics of mimicry evolution in Heliconius butterflies need to be tested in H. erato and H. melpomene specimens found in other locations other than Central and northern South Americas. For the present study, we had two motivations: (1) compare the population structure of H. erato and H. melpomene given the highly fragmented Brazil s Atlantic Forest habitat; and (2) studying population structure of co-mimics could give us insights into the dynamics of mimicry evolution. For this, we analysed the spatial structure and connectivity of eight populations of Heliconius butterflies, in a total of 137 H. erato specimens and 145 H. melpomene specimens, using nine microsatellites loci, 1144 AFLPs markers and 282 mitochondrial DNA sequences. In general, both species exhibited evidence of population subdivision but no isolation by distance indicating some extent of genetic differentiation among populations. Contrary to Kronforst & Gilbert s (2008) Costa Rican Heliconius, H. melpomene exhibited more genetic differentiation than H. erato based on nuclear markers. However, for mitochondrial DNA, H. erato populations showed more genetic differentiation than H. melpomene. Our results corroborate to other studies on Heliconius butterflies concerning the pronounced population subdivision and local genetic drift found in this genus. Nevertheless, the pattern of this differentiation varies significantly from the pattern found in studies conducted in Central America, where H. erato is generally more differentiated and structured than H. melpomene, based on nuclear markers. This different pattern may reflect different evolutionary histories of Heliconius species in Northeastern Brazil s Atlantic Forest